Detection of Brucella Infections from Clinically Suspected Cases of Brucellosis in Garmain City- Sulaimani Province Kurdistan- Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Brucellosis is a zoonotic disease transmitted between animals and humans by contaminated food, direct contact with an affected animal, or inhalation of aerosols. The research was for the period October 2019 to March 2020, 67vein blood samples of clinically suspected brucellosis (Malta fever) and 20 from healthy persons as control were tested. Control samples showed negative for brucellosis infection when serological testing was performed. while out of 67 suspected patients, 14 were significantly positive for Rose Bengal at titer (160), 39 positive for ELISA (37 for IgG and 2 for IgM). Out of 37 positive samples for IgG by ELISA, only seven samples were positive for Rose Bengal while two positive samples for IgM was negative for Rose Bengal.